2015
DOI: 10.18517/ijaseit.5.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Nutmeg (Myristicin): A Review

Abstract: In this paper a detailed review of myristicin is reported. Numerous literatures report that myristicin is responsible for hallucinogenic effects, which induced by the consumption of nutmeg due to its metabolism structure of 3-methoxy-4,5methylendioxyamphetamine (MMDA). Minimum dosage of nutmeg that can cause psychogenic effect is 5 g (ground nutmeg) with 1 to 2 mg myristicin content and this dosage is considered as 'toxic dose'. At higher dosage of myristicin death may occur. Additionally, Myristicin poisoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Other sesquiterpenes present in CEO with biologic activity are drimenol and drimenin, which were insecticidal against S. granarius [25], while the phenylpropanoid myristicin was larvicidal towards A. aegypti [74] and Spilarctia obliqua (Walker) (Lepidoptera: Erebidae) [75]. Myristicin has been described for its synergistic activity [76] as occurs with safrole, which is a precursor in the synthesis of the insecticide synergist piperonyl butoxide [77] and acts as a natural antifeedant [78].…”
Section: Discussionmentioning
confidence: 99%
“…Other sesquiterpenes present in CEO with biologic activity are drimenol and drimenin, which were insecticidal against S. granarius [25], while the phenylpropanoid myristicin was larvicidal towards A. aegypti [74] and Spilarctia obliqua (Walker) (Lepidoptera: Erebidae) [75]. Myristicin has been described for its synergistic activity [76] as occurs with safrole, which is a precursor in the synthesis of the insecticide synergist piperonyl butoxide [77] and acts as a natural antifeedant [78].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, myristicin is slightly capable of inhibiting the enzyme monoamine oxidase (MAO), which would cause pro-serotoninergic effects and cardiovascular symptoms. Studies have shown that myristicin is able to promote anxiogenesis and affect motor actions and it is suggested that it is able to modulate GABA receptors, possibly acting as an antagonist, generating anxiety [11][12][13][14]. Myristicin is metabolized in the liver by enzymes of the cytochrome P450 complex.…”
Section: Metabolization and Toxicity Of Myristicinmentioning
confidence: 99%
“…Therefore, inducing substances of the CYP1A group may facilitate the formation of reactive metabolites and increase the risk of toxicity related to myristicin. However, myristicin was also evaluated for its likely ability to inhibit CYP complex enzymes, and the results showed that myristicin exerts some inhibitory effect on human CYP2E1, CYP2C19, and CYP1A2 but exerts the strongest inhibitory effect on CYP1A2 [9,10,13].…”
Section: Metabolization and Toxicity Of Myristicinmentioning
confidence: 99%
“…There are well-documented reports of the acute toxicity of nutmeg. [50][51][52] Daily intake of myristicin by ingestion from all sources is estimated to not exceed 1 mg. 2 Myristicin production or distribution is not regulated; moreover, natural and synthetic sources of myristicin are all generally recognized as safe. 15 Because of its widespread use and structural similarity to other alkenylbenzene flavoring agents such as eugenol, methyleugenol, isoeugenol, estragole, and safrole, some of which have exhibited carcinogenic activity in rodents, 57; 58; 88-90 NTP characterized the toxicological effects of myristicin administration in 3-month studies in male and female F344/NTac rats and B6C3F1/N mice.…”
Section: Discussionmentioning
confidence: 99%